Haptoglobin genotype is associated with increased endothelial dysfunction serum markers in type 1 diabetes. (6th August 2015) - Llauradó, Gemma; Gutiérrez, Cristina; Giménez‐Palop, Olga; Cano, Albert; Pareja, Rocío; Berlanga Escalera, Eugenio; González‐Sastre, Montse; Vendrell, Joan; González‐Clemente, José‐Miguel
Abstract Background To evaluate the genotype‐driven effect of haptoglobin (Hp) in patients with type 1 diabetes without clinical cardiovascular (CV) disease, considering endothelial dysfunction (ED) and arterial stiffness (AS). Material and methods About 137 patients with type 1 diabetes (duration ≥ 5 years) and 68 age‐ and sex‐matched controls were evaluated for the following: (i) smoking, alcohol intake, BMI, blood pressure, fasting plasma glucose, HbA1c and lipid profile; (ii) microvascular complications; (iii) serum markers of ED (ICAM‐1, VCAM‐1 and E‐selectin); (iv) AS, assessed as aortic pulse wave velocity (aPWV); and (v) Hp genotype. Results The prevalence of the 1/1, 2/1 and 2/2 Hp genotypes was 28·5%, 46·7% and 24·8% in patients with type 1 diabetes and 20·9%, 38·8% and 40·3% in controls, respectively. No differences were found in classical CV risk factors between patients homozygous for allele 2 and the remaining genotypes, both in patients with type 1 diabetes and controls. Patients with type 1 diabetes carrying the Hp2/2 genotype had higher concentrations of ICAM‐1 (65·1 (56·7–76·0) ng/mL vs. 59·0 (51·7–69·3) ng/mL; P = 0·033) and sVCAM‐1 (1133·1 (884·6–1458·6) ng/mL vs. 956·4 (738·5–1206·1) ng/mL; P = 0·040) than those without it. The Hp2/2 genotype remained independently associated with ED after adjusting for CV risk factors (P = 0·038). No significant differences were found for aPWV between Hp genotypes. Conclusions Endothelial dysfunction may be influenced by Hp2/2 genotype in patients with type 1 diabetes with independence of classical CV risk factors.